Quantitative stability analysis of STATCOM in voltage control mode and Enhanced control method based on voltage feedforward - Song Zhang; Yandong Chen; Qianyuan Li; Zhiwei Xie; Youze Fu; Wenhua Wu (International Journal of Electrical Power & Energy Systems)
STATCOM is a crucial device for reactive power compensation and voltage regulation. However, under weak grid conditions, oscillations may arise during voltage control (VC) mode operation due to the AC Voltage Controller (AVC), potentially jeopardizing system stability. This paper presents a comprehensive dq-frame small-signal admittance model of STATCOM operating in VC mode. Through analysis, it is found that the AVC loop significantly amplifies the magnitude of the coupling admittance Yqd and strengthens the negative resistance–capacitance characteristics. Quantitative stability analysis results indicate that the STATCOM in VC mode exhibits reduced stability under weak grid conditions, limiting the bandwidth of both the DC voltage and phase-locked loops. Among the factors contributing to instability, the coupling admittance (Yqd and Ydq) is the dominant factor, while the influence of the diagonal admittance (Ydd and Yqq) is relatively minor. To mitigate these stability issues, we propose an optimized voltage feedforward control strategy that can effectively reduce the mid- to high-frequency amplitude of Yqd, thereby improving the stability of STATCOM in VC mode under weak grid conditions while ensuring dynamic performance. Experimental validation confirms the reliability of both the proposed stability analysis methodology and the control strategy, demonstrating a significant improvement in STATCOM stability under weak grid conditions.© 2017 Elsevier Inc. All rights reserved.